Faktor Yang Mempengaruhi Loyalitas Pelanggan (Kepuasan Pelanggan Sebagai Variabel Moderating) Perspektif Ekonomi Islam - Ivan Fadilla Budi Wardana; Sri Eka Astutiningsih (ITB AAS INDONESIA Surakarta, 2022)
This study is a quantitative study that aims to examine the factors that influence customer loyalty with customer satisfaction as a moderating variable in the perspective of Islamic economics. These factors are product quality, business location, product price, service quality and brand image on customer loyalty with customer satisfaction as a moderating variable in Raos Kopi Tulungagung. The population of this study amounted to 215 people who were taken from customers of Raos Kopi Tulungagung. The research sample was determined by simple random sampling technique, namely taking samples from the entire population. The resource obtained from interviews, questionnaires and documentation. The resource analysis method used is Moderating Regression Analysis (MRA). This study shows Results (1). Product quality has no significant effect on customer loyalty, (2). Business location, product price, service quality and brand image have a significant effect on customer loyalty, (3). Product quality, business location and service quality have no significant effect on customer satisfaction, (4). Product prices and brand image have a significant effect on customer satisfaction, (5). Product quality, product price, service quality, product quality on customer satisfaction, product price on customer satisfaction and service quality on customer satisfaction have no significant effect on customer loyalty. Factors that influence customer loyalty with customer satisfaction as moderating variables in the Islamic perspective are business location, brand image, business location on customer satisfaction, brand image on customer satisfaction have a significant effect on customer loyalty with customer satisfaction as a moderating variable on Raos Kopi Tulungagung. This research is expected to be a reference and evaluation for Muslim business actors in improving their business.